Effect of Green Marketing on Purchasing Decisions on Avoskin Products - Salma Hanifa; Agustina Widi Palupi; Alfa Chasanah (Business Review and Case Studies, 2024)
Background: The increase in waste in the beauty industry has prompted consumers to consider environmental issues when shopping, evidenced by the rise in individuals willing to pay more for green products. Meanwhile, manufacturers respond to this through green marketing strategies aligned with the Triple Bottom Line (3P) framework. Purpose: This study aims to analyze the characteristics of consumers who purchase Avoskin products and analyze the influence of green knowledge and green marketing mix on purchasing decisions on Avoskin products. Design/methodology/approach: This research was conducted in June 2023 through online questionnaires which were distributed through social media to 201 Avoskin beauty product users, this number of respondents has been in accordance with the 10-Times Rule theory. The data were processed using descriptive analysis and SEM PLS in the SmartPLS 3 application. Findings/results: The results showed that green knowledge, green products, green prices, green places, and green promotions have a positive effect on consumer purchasing decisions, but only green promotions have a significant impact. Most consumers recognize Avoskin through green promotions that have been carried out, such as introducing environmentally friendly concepts and green lifestyles. Conclusion: The study found that the green marketing mix positively influences purchasing decisions, with green promotions having the most significant impact among Avoskin consumers. However, while green knowledge also has a positive effect, it does not significantly moderate the relationship between green marketing and purchasing decisions. These findings suggest that targeted green marketing strategies, particularly those focused on promotions, are essential for enhancing consumer engagement and driving sustainable purchasing behavior in the beauty industry.Originality/value (State of the art): This study breaks new ground by pinpointing the pivotal role of green promotions in shaping consumer buying decisions in Indonesia's beauty sector, an area less explored in existing research. It provides fresh insights into the influence of green marketing elements on eco-conscious youth, offering a nuanced perspective that previous studies have overlooked. By emphasizing the strategic importance of promotions, this research significantly advances the discourse on effective green marketing strategies. Keywords: avoskin, green knowledge, green marketing, green marketing mix, sem-pls